Preparation method of low-cost high-efficiency large-layer-thickness selective laser melting die steel
By adopting large-particle powder and large-layer thickness processes in the selected laser melting technology, combined with ultrasonic vibration-assisted methods, the problems of high cost, low efficiency and low quality in the prior art are solved, and low cost, high efficiency and high density mold steel preparation is achieved.
Patent Information
- Application Number
- CN202411814235.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-08
AI Technical Summary
The existing laser melting technology in selected areas has problems such as high cost, low forming efficiency and poor forming quality in large-scale industrial applications. Especially when using large-particle mold steel powder and large-layer thick processes, problems such as uneven powder distribution, unstable melt pool and pore formation are prone to occur.
The process of large powder particle size (15-106μm) and large layer thickness (80-120μm) is adopted, combined with ultrasonic vibration-assisted selection laser melting forming method, through the reasonable matching of coarse and fine powder particles and the action of ultrasonic waves, the uniformity and density of powder laying are improved and the stability of the melt pool is enhanced.
On the premise of ensuring the forming quality, the production cost is reduced and the forming efficiency is improved, and the mold steel preparation with high density and high mechanical properties is achieved, which is suitable for large-scale production needs.
Smart Images

Figure CN119772198A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of additive manufacturing, and in particular relates to a method for preparing a low-cost, high-efficiency, large-layer-thickness selective-area laser-melting die steel. Background Art
[0002] In modern manufacturing, mold steel is widely used in the manufacture of molds, tools and mechanical parts. At present, the production methods of mold steel mainly rely on traditional processing methods such as milling, grinding and electrospark machining. Although these methods are mature in technology, they are inefficient when faced with complex shapes or small batch production, and usually result in a large amount of material waste. In addition, traditional processing methods are time-consuming, have limited control over the mechanical properties and surface quality of the material, and especially when performing fine processing, the labor and equipment costs increase significantly.
[0003] Corrax stainless steel (SS-CX) mold steel is a new type of martensitic aged stainless steel. Ultra-low carbon content is a significant feature of CX stainless steel, which can reduce cracking sensitivity and inhibit pore formation during the manufacturing process. CX stainless steel manufactured by Selective Laser Melting (SLM) has high strength, hardness and good corrosion resistance. Laser power, laser scanning speed and laser scanning spacing are important process parameters in additive manufacturing, which determine the microstructure of the material and affect the defects of the material. Among them: density is the main factor affecting the mechanical properties of additively manufactured parts.
[0004] In recent years, SLM, as an advanced additive manufacturing method, has gradually been applied to the production of mold steel. This technology can achieve rapid prototyping of complex geometric shapes by melting metal powder layer by layer. However, there are still several major problems in the large-scale industrial application of selective laser melting technology:
[0005] High cost: The existing mold steel powder has a small particle size. Although it can ensure a certain forming quality, its manufacturing cost is high. Especially in large-scale production, the price of the material becomes an important factor.
[0006] Low forming efficiency: Existing SLM processes usually require a smaller layer thickness (such as 20-50μm) to ensure forming accuracy, which limits the forming efficiency. The smaller the layer thickness, the more layers need to be melted, and the melting time increases significantly, resulting in a longer production cycle.
[0007] Poor forming quality: The use of large-particle mold steel powder effectively reduces material costs; the use of large layer thickness process significantly improves the forming efficiency of the SLM process. However, as the powder particle size increases, the powder is prone to uneven distribution during powder spreading. Large particles with large gravity will gradually sink to the bottom, weakening the role of small particles in penetrating and filling the gaps. The powder bed has many gaps and is not dense. The formed molten pool is non-continuous, and the powder has a small specific surface area and absorbs less energy, resulting in some large-particle powder not being completely melted, forming a spheroidization phenomenon. Especially after the next layer of large-layer thick powder is spread, the powder layer thickness is more uneven. Affected by the Gaussian distribution of laser energy, the powder at the edge of the molten pool is not completely melted and will not be remelted for the second time, which aggravates the appearance of spheroidization and pores, resulting in a decrease in the density of the parts. In addition, as the layer thickness increases, the window of laser process parameters becomes narrower, which not only limits the printing efficiency, but also makes it difficult to achieve a high forming density. When using low laser power density, heat is difficult to accumulate and powder is difficult to melt; when using high laser power density to melt metal powder, smaller powder particles are vaporized in large quantities, resulting in the formation of small holes and highly unstable laser reflection in the holes, making the formed molten pool extremely unstable, and exacerbating phenomena such as spatter, porosity and other defects, resulting in poor forming quality.
[0008] Therefore, it is urgent to improve the uniformity and density of powder spreading and the stability of the molten pool, so as to improve the forming density and mechanical properties of parts under the process of large particle size powder and large layer thickness. Summary of the invention
[0009] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a low-cost, high-efficiency, large-layer-thickness selective laser melting die steel preparation method, which uses die steel powder with large powder particle size (15-106μm) as raw material, combined with a large layer thickness (80-120μm) process, and adopts a selective laser melting forming method assisted by ultrasonic vibration, which reduces production costs and improves forming efficiency while ensuring forming quality.
[0010] The inventive concept of the present invention is: combining large-particle powder and a specific large-layer thickness process, through the combination of powders of different particle sizes and ultrasonic assistance to achieve the reduction of production costs, improve forming efficiency and forming quality. Among them: the coarse and fine powder particles are reasonably matched, the fluidity and loose density of the powder are better, the geometric gap can be reduced, and high-density powder spreading can be achieved. Ultrasonic vibration mainly induces two main effects: acoustic streaming and cavitation. When acoustic streaming and cavitation affect the Marangoni flow in the molten pool, additional stirring and mixing are used to promote the movement of materials in the liquid molten pool and the fluidity of the molten pool to attract powder, thereby generating less splashing, thereby improving the forming quality. At the same time, ultrasonic vibration causes periodic displacement of the powder bed, reduces the recoil pressure of the interaction between the laser and the powder particles, and the density and heat in the molten pool are more uniform and stable. Large layer thickness is conducive to improving printing speed and efficiency, and meets the needs of large-scale production. Therefore, the preparation method of the present invention can simultaneously have the low cost, high efficiency and high density of selective laser melting of mold steel powder, effectively reduce the printing time and material cost of parts, improve the 3D printing forming efficiency, while taking into account the forming quality and mechanical properties of the part surface, which is of great significance for the preparation of new high-end molds.
[0011] To solve the above technical problems, the first aspect of the present invention provides a method for preparing mold steel, wherein the raw materials for preparing the mold steel include a first mold steel powder and a second mold steel powder, the particle size of the first mold steel powder is 15-53μm, and the particle size of the second mold steel powder is 53-106μm; the mold steel is formed by selective laser melting assisted by ultrasonic vibration, and the powder thickness of the selective laser melting is 80-120μm.
[0012] In some embodiments of the present invention, the first mold steel powder and the second mold steel powder are both made of Corrax SS-CX mold steel powder, which is a gas-atomized spherical powder with excellent wear resistance and mechanical properties and is suitable for high-strength applications. At the same time, selecting some large-particle powder is conducive to reducing material costs.
[0013] In some embodiments of the present invention, the chemical composition of the first mold steel powder is as follows by weight percentage: Cr11.96%, Ni 9.13%, Al 1.47%, Mo 1.43%, Si 0.23%, Mn 0.22%, P 0.011%, C 0.006%, and the balance is Fe.
[0014] In some embodiments of the present invention, the chemical composition of the second mold steel powder is as follows by weight percentage: Cr 12.00%, Ni 9.20%, Al 1.65%, Mo 1.40%, Si 0.25%, Mn 0.22%, and the balance is Fe.
[0015] In some embodiments of the present invention, the mass ratio of the first mold steel powder to the second mold steel powder is (0.8-1.2):1.
[0016] In some embodiments of the present invention, the mass ratio of the first mold steel powder to the second mold steel powder is 1:1.
[0017] In some embodiments of the present invention, the powder coating thickness of the selective laser melting forming is 100-120 μm.
[0018] In some embodiments of the present invention, the laser power of the selective laser melting is 350-500 W. The specific power is optimized according to the material powder layer thickness and printing speed to ensure sufficient melting.
[0019] In some embodiments of the present invention, the laser power of the selective laser melting is 400-450W.
[0020] In some embodiments of the present invention, the laser scanning speed of the selective laser melting forming is 700-1200 mm / s. The optimal laser scanning speed is determined through experiments to improve the forming efficiency, ensure the melting uniformity, and avoid the unmelted area.
[0021] In some embodiments of the present invention, the laser scanning speed of the selective laser melting is 800-1150 mm / s.
[0022] In some embodiments of the present invention, the laser scanning spacing of the selective laser melting forming is 0.09-0.160 mm. The laser scanning spacing is optimized to ensure sufficient fusion between each layer of material, reduce porosity, and improve sample density.
[0023] In some embodiments of the present invention, the laser scanning spacing of the selective laser melting forming is 0.095-0.100 mm.
[0024] In some embodiments of the present invention, the laser spot of the selective laser melting is 100-150 μm.
[0025] In some embodiments of the present invention, the energy density of the selective laser melting forming is 30.43-71.94 J / mm 3 .
[0026] In some embodiments of the present invention, the energy density of the selective laser melting is 30.43-51.46 J / mm 3 .
[0027] In some embodiments of the present invention, the ultrasonic vibration-assisted ultrasound frequency is 20-50 KHz, and the amplitude is 2-9 μm.
[0028] In some embodiments of the present invention, the ultrasonic vibration-assisted ultrasound frequency is 25-45 KHz, and the amplitude is 2-9 μm.
[0029] In some embodiments of the present invention, the method for preparing the mold steel comprises the following steps:
[0030] (1) mixing a first mold steel powder and a second mold steel powder to obtain a mixed mold steel powder;
[0031] (2) The mixed mold steel powder is laid on a stainless steel substrate, and printed and formed by a selective laser melting method with the assistance of ultrasonic vibration to obtain the mold steel.
[0032] In some embodiments of the present invention, the step of preheating the stainless steel substrate is further included before the selective laser melting, and the preheating temperature is 80-120° C. Preheating the stainless steel substrate before the selective laser melting is beneficial to reducing the transverse and longitudinal temperatures of the junction between the printed layer and the substrate during the cooling process, thereby effectively reducing the cracking sensitivity of the mold steel.
[0033] In some embodiments of the present invention, the method for preparing the mold steel comprises the following steps:
[0034] (1) Optimizing process parameters: Through experimental research, the process parameters of selective laser melting are optimized. The optimized process parameters are: laser power of 350-500W, laser scanning speed of 700-1200mm / s, laser scanning spacing of 0.09-0.160mm, powder layer thickness of 80-120μm, laser spot diameter of 100-150μm, and laser wavelength of 1070nm;
[0035] (2) Preparation of bulk samples: 304 stainless steel was used as the substrate and SS-CX aerosolized spherical powder was used as the raw material. Based on the process parameters obtained in step (1), the laser power, laser scanning speed, laser scanning spacing, laser scanning strategy (strip scanning, the scanning direction between each layer rotated 67°), wind field parameters (circulating air volume of 40-55, cabin pressure of 20-25 mbar) and powder layer thickness were set, and then the bulk sample was prepared. The size of the bulk sample was 15×15×15 mm. 3 ;
[0036] (3) Preparing the forming chamber: Selective laser melting forming equipment is used to prepare block samples. Before starting the printing task, preparatory work is performed; first, the substrate is installed, and the powder is added and pre-spread on the substrate (the Hall flow rate of the powder is 15.47-20.86s / 50g, and the loose density is 3.92-4.55g / cm 3 ), then wipe the laser lens with a dust-free cloth, close the chamber door, start vacuuming and introduce inert gas into the forming chamber until the oxygen concentration is lower than 100ppm, and preheat the substrate at the same time;
[0037] (4) Laser melting forming: According to the designed laser scanning strategy, wind field parameters, and set processing parameters, the pre-laid SS-CX mold steel powder is melted, and during the printing process, ultrasonic vibration is added to assist, with an ultrasonic frequency of 20-50KHz and an amplitude of 2-9μm; a part layer is obtained through rapid melting and solidification, and then the substrate is lowered by a set processing layer thickness, and powder is re-laid on the previous solidified alloy layer. The laser scans the laid powder again, and each layer only needs one laser scan to get a flat alloy melt layer;
[0038] (5) Repeat the operation of step (4) to re-powder and scan, and repeat this cycle, scanning and processing layer by layer until the SS-CX mold steel powder scanned by the laser reaches the designed block size and shape;
[0039] (6) After all samples are prepared on the SLM printing device, the substrate and the sample are taken out, and the sample is separated from the substrate using a wire cutting device to obtain the mold steel sample.
[0040] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0041] The present invention combines large-particle powder and a specific large-layer thickness process, and achieves reduced production costs, improved forming efficiency and forming quality through the combination of powders of different particle sizes and ultrasonic assistance. Among them: coarse and fine powder particles are reasonably matched, the fluidity and loose density of the powder are better, the geometric gap is reduced, and high-density powder spreading is achieved. Ultrasonic vibration causes periodic displacement of the powder bed, reduces the recoil pressure of the interaction between the laser and the powder particles, and the density and heat in the molten pool are more uniform and stable. At the same time, ultrasonic vibration can induce acoustic flow and cavitation, reduce splashing, and thus improve the forming quality. Large layer thickness is conducive to improving printing speed and efficiency, and meets the needs of large-scale production. Therefore, the preparation method of the present invention can simultaneously combine the low cost, high efficiency and high density of selective laser melting of mold steel powder, effectively reducing the printing time and material cost of parts, improving the 3D printing forming efficiency, while taking into account the forming quality and mechanical properties of the surface of the parts, which is of great significance for the preparation of new high-end molds. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a metallographic diagram of the density of the mold steel prepared in Comparative Example 1;
[0043] Figure 2 This is a metallographic diagram of the density of the mold steel prepared in Comparative Example 2;
[0044] Figure 3 This is a metallographic diagram of the density of the mold steel prepared in Comparative Example 9;
[0045] Figure 4 This is the density metallographic diagram of the mold steel prepared in Example 1;
[0046] Figure 5 This is the density metallographic diagram of the mold steel prepared in Example 9;
[0047] Figure 6 This is the density metallographic diagram of the mold steel prepared in Example 17. DETAILED DESCRIPTION
[0048] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0049] Example 1
[0050] A method for manufacturing mold steel comprises the following steps:
[0051] (1) Optimization of process parameters: The process parameters of selective laser melting were optimized through experimental research. The optimized process parameters are as follows: laser power of 408 W, laser scanning speed of 858 mm / s, laser scanning spacing of 105 μm, powder layer thickness of 80 μm, laser spot diameter of 100-150 μm, laser wavelength of 1070 nm, and energy density of 56.61 J / mm 3 ;
[0052] (2) Preparation of bulk samples: 304 stainless steel was used as the substrate, and 50% of fine powder with a particle size range of 15-53 μm and 50% of coarse powder with a particle size range of 53-106 μm were used. After the coarse and fine powders were fully mixed, D10 = 25.36 μm, D50 = 60.47 μm, D90 = 91.66 μm, the Hall flow rate was 20.87 s / 50 g, and the bulk density was 4.55 g / cm3 SS-CX mold steel powder, based on the process parameters obtained in step (1), set the laser scanning strategy (strip scanning, the scanning direction between each layer rotates 67°) and wind field parameters (circulation air volume is 40-55, cabin pressure is 20-25mbar), and then prepare the block sample, where the block sample size is 15×15×15mm 3 ;
[0053] (3) Prepare the forming chamber: Use the selective laser melting forming equipment to prepare the block sample. Before starting the printing task, perform the preparatory work; first install the substrate, add the powder and pre-spread the powder on the substrate, then wipe the laser lens with a dust-free cloth, close the chamber door, start vacuuming and introduce inert gas into the forming chamber until the oxygen concentration is less than 100 ppm, and preheat the substrate to 80-120°C;
[0054] (4) Laser melting forming: According to the designed laser scanning strategy, wind field parameters, and set processing parameters, the pre-laid SS-CX mold steel powder is melted, and during the printing process, ultrasonic vibration is added to assist, with an ultrasonic frequency of 25KHz and an amplitude of 2-9μm. The generated ultrasonic vibration is transmitted to the substrate through an amplitude transformer, and vertical ultrasonic vibration is obtained on the substrate surface; a part layer is obtained through rapid melting and solidification, and then the substrate is lowered by a set processing layer thickness, and powder is re-laid on the previous solidified alloy layer. The laser scans the laid powder again, and each layer only needs one laser scan to obtain a flat alloy melt layer;
[0055] (5) Repeat the operation of step (4) to re-powder and scan, and repeat this cycle, scanning and processing layer by layer until the SS-CX mold steel powder scanned by the laser reaches the designed block size and shape;
[0056] (6) After all samples are prepared on the SLM printing device, the substrate and the sample are taken out, and the sample is separated from the substrate using a wire cutting device to obtain the mold steel sample.
[0057] Embodiment 2-8
[0058] The difference between Example 2-8 and Example 1 is that the process parameters of the selective laser melting forming are different, as shown in Table 1.
[0059] Table 1:
[0060]
[0061] Example 9
[0062] A method for manufacturing mold steel comprises the following steps:
[0063] (1) Optimization of process parameters: The process parameters of selective laser melting were optimized through experimental research. The optimized process parameters are as follows: laser power of 410 W, laser scanning speed of 850 mm / s, laser scanning spacing of 100 μm, powder layer thickness of 100 μm, laser spot diameter of 100-150 μm, laser wavelength of 1070 nm, and energy density of 48.24 J / mm 3 ;
[0064] (2) Preparation of bulk samples: 304 stainless steel was used as the substrate, and 50% of fine powder with a particle size range of 15-53 μm and 50% of coarse powder with a particle size range of 53-106 μm were used. After the coarse and fine powders were fully mixed, D10 = 25.36 μm, D50 = 60.47 μm, D90 = 91.66 μm, the Hall flow rate was 20.87 s / 50 g, and the bulk density was 4.55 g / cm 3 SS-CX mold steel powder, based on the process parameters obtained in step (1), set the laser scanning strategy (strip scanning, the scanning direction between each layer rotates 67°) and wind field parameters (circulation air volume is 40-55, cabin pressure is 20-25mbar), and then prepare the block sample, where the block sample size is 15×15×15mm 3 ;
[0065] (3) Prepare the forming chamber: Use the selective laser melting forming equipment to prepare the block sample. Before starting the printing task, perform the preparatory work; first install the substrate, add the powder and pre-spread the powder on the substrate, then wipe the laser lens with a dust-free cloth, close the chamber door, start vacuuming and introduce inert gas into the forming chamber until the oxygen concentration is less than 100 ppm, and preheat the substrate to 80-120°C;
[0066] (4) Laser melting forming: According to the designed laser scanning strategy, wind field parameters, and set processing parameters, the pre-laid SS-CX mold steel powder is melted, and during the printing process, ultrasonic vibration is added to assist, with an ultrasonic frequency of 35KHz and an amplitude of 2-9μm. The generated ultrasonic vibration is transmitted to the substrate through an amplitude transformer, and vertical ultrasonic vibration is obtained on the substrate surface; a part layer is obtained through rapid melting and solidification, and then the substrate is lowered by a set processing layer thickness, and powder is re-laid on the previous solidified alloy layer. The laser scans the laid powder again, and each layer only needs one laser scan to obtain a flat alloy melt layer;
[0067] (5) Repeat the operation of step (4) to re-powder and scan, and repeat this cycle, scanning and processing layer by layer until the SS-CX mold steel powder scanned by the laser reaches the designed block size and shape;
[0068] (6) After all samples are prepared on the SLM printing device, the substrate and the sample are taken out, and the sample is separated from the substrate using a wire cutting device to obtain the mold steel sample.
[0069] Examples 10-16
[0070] The difference between Examples 10-16 and Example 9 is that the process parameters of the selective laser melting forming are different, as shown in Table 2.
[0071] Table 2:
[0072]
[0073]
[0074] Embodiment 17
[0075] A method for manufacturing mold steel comprises the following steps:
[0076] (1) Optimization of process parameters: The process parameters of selective laser melting were optimized through experimental research. The optimized process parameters are as follows: laser power of 450 W, laser scanning speed of 950 mm / s, laser scanning spacing of 100 μm, powder layer thickness of 120 μm, laser spot diameter of 100-150 μm, laser wavelength of 1070 nm, and energy density of 39.47 J / mm 3 ;
[0077] (2) Preparation of bulk samples: 304 stainless steel was used as the substrate, and 50% of fine powder with a particle size range of 15-53 μm and 50% of coarse powder with a particle size range of 53-106 μm were used. After the coarse and fine powders were fully mixed, D10 = 25.36 μm, D50 = 60.47 μm, D90 = 91.66 μm, the Hall flow rate was 20.87 s / 50 g, and the bulk density was 4.55 g / cm 3 SS-CX mold steel powder, based on the process parameters obtained in step (1), set the laser scanning strategy (strip scanning, the scanning direction between each layer rotates 67°) and wind field parameters (circulation air volume is 40-55, cabin pressure is 20-25mbar), and then prepare the block sample, where the block sample size is 15×15×15mm 3 ;
[0078] (3) Prepare the forming chamber: Use the selective laser melting forming equipment to prepare the block sample. Before starting the printing task, perform the preparatory work; first install the substrate, add the powder and pre-spread the powder on the substrate, then wipe the laser lens with a dust-free cloth, close the chamber door, start vacuuming and introduce inert gas into the forming chamber until the oxygen concentration is less than 100 ppm, and preheat the substrate to 80-120°C;
[0079] (4) Laser melting forming: According to the designed laser scanning strategy, wind field parameters, and set processing parameters, the pre-laid SS-CX mold steel powder is melted, and during the printing process, ultrasonic vibration is added to assist, with an ultrasonic frequency of 45KHz and an amplitude of 2-9μm. The generated ultrasonic vibration is transmitted to the substrate through an amplitude transformer, and vertical ultrasonic vibration is obtained on the substrate surface; a part layer is obtained through rapid melting and solidification, and then the substrate is lowered by a set processing layer thickness, and powder is re-laid on the previous solidified alloy layer. The laser scans the laid powder again, and each layer only needs one laser scan to obtain a flat alloy melt layer;
[0080] (5) Repeat the operation of step (4) to re-powder and scan, and repeat this cycle, scanning and processing layer by layer until the SS-CX mold steel powder scanned by the laser reaches the designed block size and shape;
[0081] (6) After all samples are prepared on the SLM printing device, the substrate and the sample are taken out, and the sample is separated from the substrate using a wire cutting device to obtain the mold steel sample.
[0082] Examples 18-24
[0083] The difference between Examples 18-24 and Example 17 is that the process parameters of the selective laser melting forming are different, as shown in Table 3.
[0084] Table 3:
[0085]
[0086] Comparative Example 1
[0087] A method for manufacturing mold steel comprises the following steps:
[0088] (1) Optimization of process parameters: The process parameters of selective laser melting were optimized through experimental research. The optimized process parameters are as follows: laser power of 300 W, laser scanning speed of 800 mm / s, laser scanning spacing of 90 μm, powder layer thickness of 50 μm, laser spot diameter of 100-150 μm, laser wavelength of 1070 nm, and energy density of 83.33 J / mm 3 ;
[0089] (2) Preparation of bulk samples: 304 stainless steel was used as the substrate, 100% fine powder with a particle size range of 15-53 μm was used, D10 = 19 μm, D50 = 32.7 μm, D90 = 56.2 μm, Hall flow rate 18.5 s / 50 g, and bulk density 3.92 g / cm 3SS-CX mold steel powder, based on the process parameters obtained in step (1), set the laser scanning strategy (strip scanning, the scanning direction between each layer rotates 67°) and wind field parameters (circulation air volume is 40-55, cabin pressure is 20-25mbar), and then prepare the block sample, where the block sample size is 15×15×15mm 3 ;
[0090] (3) Prepare the forming chamber: Use the selective laser melting forming equipment to prepare the block sample. Before starting the printing task, perform the preparatory work; first install the substrate, add the powder and pre-spread the powder on the substrate, then wipe the laser lens with a dust-free cloth, close the chamber door, start vacuuming and introduce inert gas into the forming chamber until the oxygen concentration is less than 100 ppm, and preheat the substrate to 80-120°C;
[0091] (4) Laser melting forming: According to the designed laser scanning strategy, wind field parameters, and set processing parameters, the pre-laid SS-CX mold steel powder is melted, and during the printing process, a part layer is obtained through rapid melting and solidification. Then the substrate is lowered by a set processing layer thickness, and powder is re-laid on the previous solidified alloy layer. The laser scans the laid powder again. Each layer only needs one laser scan to get a flat alloy melt layer.
[0092] (5) Repeat the operation of step (4) to re-powder and scan, and repeat this cycle, scanning and processing layer by layer until the SS-CX mold steel powder scanned by the laser reaches the designed block size and shape;
[0093] (6) After all samples are prepared on the SLM printing device, the substrate and the sample are taken out, and the sample is separated from the substrate using a wire cutting device to obtain the mold steel sample.
[0094] Comparative Examples 2-8
[0095] The difference between Comparative Examples 2-8 and Example 1 is that the process parameters of the selective laser melting forming are different, as shown in Table 4.
[0096] Table 4:
[0097]
[0098] Comparative Example 9
[0099] A method for manufacturing mold steel comprises the following steps:
[0100] (1) Optimization of process parameters: The process parameters of selective laser melting were optimized through experimental research. The optimized process parameters are as follows: laser power of 370 W, laser scanning speed of 800 mm / s, laser scanning spacing of 90 μm, powder layer thickness of 80 μm, laser spot diameter of 100-150 μm, laser wavelength of 1070 nm, and energy density of 62.24 J / mm 3 ;
[0101] (2) Preparation of bulk samples: 304 stainless steel was used as the substrate, 100% fine powder with a particle size range of 53-106 μm was used, D10 = 55.36 μm, D50 = 79.77 μm, D90 = 101.65 μm, Hall flow rate 15.47 s / 50 g, and bulk density 4.43 g / cm 3 SS-CX mold steel powder, based on the process parameters obtained in step (1), set the laser scanning strategy (strip scanning, the scanning direction between each layer rotates 67°) and wind field parameters (circulation air volume is 40-55, cabin pressure is 20-25mbar), and then prepare the block sample, where the block sample size is 15×15×15mm 3 ;
[0102] (3) Prepare the forming chamber: Use the selective laser melting forming equipment to prepare the block sample. Before starting the printing task, perform the preparatory work; first install the substrate, add the powder and pre-spread the powder on the substrate, then wipe the laser lens with a dust-free cloth, close the chamber door, start vacuuming and introduce inert gas into the forming chamber until the oxygen concentration is less than 100 ppm, and preheat the substrate to 80-120°C;
[0103] (4) Laser melting forming: According to the designed laser scanning strategy, wind field parameters, and set processing parameters, the pre-laid SS-CX mold steel powder is melted, and during the printing process, a part layer is obtained through rapid melting and solidification. Then the substrate is lowered by a set processing layer thickness, and powder is re-laid on the previous solidified alloy layer. The laser scans the laid powder again. Each layer only needs one laser scan to get a flat alloy melt layer.
[0104] (5) Repeat the operation of step (4) to re-powder and scan, and repeat this cycle, scanning and processing layer by layer until the SS-CX mold steel powder scanned by the laser reaches the designed block size and shape;
[0105] (6) After all samples are prepared on the SLM printing device, the substrate and the sample are taken out, and the sample is separated from the substrate using a wire cutting device to obtain the mold steel sample.
[0106] Comparative Examples 10-16
[0107] The difference between Comparative Examples 10-16 and Example 9 is that the process parameters of the selective laser melting forming are different, as shown in Table 5.
[0108] Table 5:
[0109]
[0110] Performance Testing
[0111] 1. Density, forming efficiency and cost-effectiveness
[0112] The mold steel samples prepared in the above-mentioned embodiments 1-24 and comparative examples 1-16 were ground using 240#, 400#, 600#, 800#, 1000#, 1500#, 2000#, and 4000# sandpaper, respectively. After polishing, they were observed using an optical microscope, and each sample was captured and photographed. Dozens of optical microscope pictures were taken, covering the polished surface as much as possible, while avoiding water stains, scratches, etc. Finally, the density was measured using ImageJ, and the forming efficiency and cost-effectiveness were calculated, wherein: the cost-effectiveness only considered the impact of material cost and forming efficiency, and did not consider the daily production costs such as labor, equipment, and equipment maintenance. The results are shown in Table 6.
[0113] Where: forming efficiency = laser scanning speed × laser scanning spacing × layer thickness.
[0114] In Comparative Examples 1-8, the price of 100% vacuum air atomized SS-CX mold steel fine powder with a particle size of 15-53 μm is 120 yuan / kg; at this time, cost-effectiveness = forming efficiency / 50 layer thickness forming efficiency = (forming efficiency / 3.60).
[0115] In Comparative Examples 9-16, the price of 100% vacuum air atomized SS-CX mold steel coarse powder with a powder particle size of 53-106μm is 100 yuan / kg. Compared with the price of 100% vacuum air atomized SS-CX mold steel fine powder with a powder particle size of 15-53μm, the material cost-effectiveness of the coarse powder is 0.17; at this time, cost-effectiveness = forming efficiency / 50 layer thickness forming efficiency + material cost-effectiveness = (forming efficiency / 3.60) + 0.17.
[0116] In Examples 1-24, the price of 100% vacuum air atomized SS-CX mold fine powder with a powder particle size of 15-53 μm is 120 yuan / kg, and the price of 100% vacuum air atomized SS-CX mold steel coarse powder with a powder particle size of 53-106 μm is 100 yuan / kg. Compared with fine powder, the material cost-effectiveness of coarse powder is 0.08; at this time, cost-effectiveness = forming efficiency / 50 layer thickness forming efficiency + material cost-effectiveness = (forming efficiency / 3.60) + 0.08.
[0117] Table 6:
[0118]
[0119]
[0120] 2. Microhardness
[0121] The high-density mold steel samples prepared in Comparative Examples 1-2, Comparative Example 9 and Example 1, Example 9 and Example 17 were tested for hardness using a microhardness tester. Multi-point tests were performed every 300 μm along the direction perpendicular to the construction, with a load of 300 g and a loading time of 20 s. The density metallographic diagrams of different parts of each sample are shown in FIG. Figure 1-6 The sample was post-heat treated at 530℃ for 3 hours, and the hardness test was carried out by the same method to obtain the post-heat treatment microhardness. The results are shown in Table 7.
[0122] Table 7:
[0123]
[0124]
[0125] From Table 6-7 and Figure 1-6 It can be seen that compared with comparative examples 9-16, in implementation examples 1-8, since the powder used is a mixture of coarse and fine powders and ultrasonic assistance is added, the uniformity and density of the powder spreading are improved, the splashing is reduced, and the stability of the molten pool is improved. In addition, the density of the samples prepared in embodiments 1-8 is higher than that of comparative examples 1-8. Example 1 is subjected to a post-heat treatment of 530°C / 3h and then air cooling, and the hardness obtained is increased from 360-370HV in the printed state to 1.5HV in the printed state. 0.3 , increased to 525-535HV 0.3 .
[0126] The difference between Example 9-16 and Example 1-8 is that the layer thickness of the sample prepared in Example 9-16 is 100 μm, the frequency of the external ultrasonic auxiliary is 35 kHz, and the energy density range with a density higher than 99.9% is 43.68 to 62.41 J / mm 3 Compared with Examples 1-8, the energy density (49.14-71.94 J / mm 3 ) range is narrowed. Example 9 was subjected to a post-heat treatment at 530°C / 3h and then air-cooled, and the hardness was increased from 370-380HV in the printed state. 0.3 , increased to 535-545HV 0.3 .
[0127] The difference between Examples 17-24 and Examples 9-16 is that the layer thickness of the samples prepared in Examples 17-24 is 120 μm, the frequency of the external ultrasonic auxiliary is 45 kHz, the energy density range of the density higher than 99.9% is 39.47 to 51.46 J / mm3, and the energy density (43.68 to 62.41 J / mm3) is higher than that in Examples 9-16. 3 ) range is narrowed. As the layer thickness increases, the energy density gradually decreases, and the process window gradually narrows. Example 17 is subjected to a post-heat treatment at 530°C / 3h, followed by air cooling, and the hardness obtained is 380-390HV in the printed state. 0.3 , increased to 555-565HV 0.3 .
[0128] Comparative Examples 1-8, the energy density range of the 80-layer thick sample with a density higher than 99.5% is 52.14-65.97 J / mm 3 The difference between Comparative Examples 9-16 and Comparative Examples 1-8 is mainly the different ranges of powder particle sizes. The density of the samples prepared in Comparative Examples 9-16 is higher than 99.5%, and the energy density range with a density higher than 99.5% is greater than the 80-layer thick sample in Comparative Examples 1-8.
[0129] from Figure 1 It can be seen that the sample density is higher under the fine powder and small layer thickness process in Comparative Example 1.
[0130] from Figure 2-3 It can be seen that in Comparative Examples 2 and 9, single fine powder and single coarse powder are combined with a large layer thickness process without external ultrasonic assistance. The powder distribution of the samples is uneven, the molten pool is unstable, obvious pores and unfused defects appear, and the density is poor.
[0131] from Figure 4 It can be seen that in Example 1, the combination of coarse and fine powders is combined with a large layer thickness process, and ultrasonic assistance is added. The sample has good powder spreading uniformity and density, improved molten pool stability, and no obvious unfused defects.
[0132] from Figure 5-6 It can be seen that, with the reasonable increase of layer thickness and ultrasonic frequency in Example 9 and Example 17, the sample density is high, achieving the goal of reducing production costs and improving forming efficiency and forming quality.
[0133] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A method for preparing mold steel, characterized in that: The raw materials for preparing the mold steel include first mold steel powder and second mold steel powder, the particle size of the first mold steel powder is 15-53 μm, and the particle size of the second mold steel powder is 53-106 μm; the mold steel is formed by selective laser melting assisted by ultrasonic vibration, and the powder thickness of the selective laser melting is 80-120 μm.
2. The method for preparing mold steel according to claim 1, characterized in that: The mass ratio of the first mold steel powder to the second mold steel powder is (0.8-1.2):
1.
3. The method for preparing mold steel according to claim 1, characterized in that: The laser power of the selective laser melting forming is 350-500W.
4. The method for preparing mold steel according to claim 1, characterized in that: The laser scanning speed of the selective laser melting forming is 700-1200 mm / s.
5. The method for preparing mold steel according to claim 1, characterized in that: The laser scanning spacing of the selective laser melting forming is 0.09-0.160 mm.
6. The method for preparing mold steel according to claim 1, characterized in that: The laser spot of the selective laser melting forming is 100-150 μm.
7. The method for preparing mold steel according to claim 1, characterized in that: The energy density of the selective laser melting forming is 30.43-71.94 J / mm 3 .
8. The method for preparing mold steel according to claim 1, characterized in that: The ultrasonic vibration-assisted ultrasonic frequency is 20-50 KHz, and the amplitude is 2-9 μm.
9. The method for preparing mold steel according to claim 1, characterized in that: The preparation method comprises the following steps: (1) mixing a first mold steel powder and a second mold steel powder to obtain a mixed mold steel powder; (2) The mixed mold steel powder is laid on a stainless steel substrate, and printed and formed by a selective laser melting method with the assistance of ultrasonic vibration to obtain the mold steel.
10. The method for preparing mold steel according to claim 9, characterized in that: Before performing the selective laser melting, the method further includes preheating the stainless steel substrate, wherein the preheating temperature is 80-120°C.
Citation Information
Cited By
Additive manufacturing method, workpiece, system and application for partitioned melting of coarse powder and fine powder
CN122125244A